Ionic polymers based on titanium oxide clusters and their synthesis and applications
The ionic titanium oxide cluster polymer was prepared by reacting titanium oxide cluster compounds with 1,4-dibromo-2-butene, which solved the problem of poor film formation of titanium oxide clusters, achieved efficient electron transport layer materials, and improved the energy conversion efficiency of polymer solar cells.
Patent Information
- Application Number
- CN202211120641.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-09-15
AI Technical Summary
The existing titanium oxygen cluster has poor film formation and is sensitive to the concentration of electron transport layer solution, which limits its wide application in polymer solar cells.
The ionic titanium oxide cluster polymer was prepared by reacting with 1,4-dibromo-2-butene by low temperature heating, and used as an electron transport layer material for polymer solar cells.
Good alcohol solubility, excellent film formation and appropriate energy level matching are achieved, and the energy conversion efficiency of organic solar cells is improved to reach 17.9% or above.
Smart Images

Figure CN115505002B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a titanium oxide cluster compound and an ionic titanium oxide cluster polymer as a precursor thereof, and application of the titanium oxide cluster polymer as an electron transport layer material in a polymer solar cell, belonging to the technical field of semiconductor functional materials. Background Art
[0002] Polymer solar cells have received extensive attention in recent years due to their advantages such as being light, cheap, and processable in solution. The efficiency of single-cell polymer batteries has also been rising year by year, which is inseparable from the continuous optimization of device structures and the continuous development of donor and acceptor materials and interface layer materials. As a new type of electron transport layer material, the application of ionic polymers in organic solar cells is becoming increasingly prominent. Among them, titanium oxide cluster-based ionic polymers have the advantages of adjustable surface ligands of the titanium oxide cluster core, simple post-synthesis process, strong solution processability, good film-forming properties, and low cost. Therefore, they are very suitable as electron transport layer materials for organic solar cells, and their commercial application prospects are very promising. However, since the above-mentioned neutral titanium oxide clusters have poor film-forming properties and are sensitive to the concentration of the electron transport layer solution, this has largely limited the widespread application of electron transport layer materials in solar cells. Summary of the invention
[0003] In order to overcome the above problems and realize the preparation of high-performance solar cells, the present invention provides a method for preparing a titanium oxide cluster ion polymer and its application as an electron transport layer material in a polymer solar cell.
[0004] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0005] The first aspect of the present invention provides a titanium oxide cluster compound and an ionic titanium oxide cluster polymer using the titanium oxide cluster compound as a precursor.
[0006] A. The structural formula of titanium oxide cluster compound is Ti4O2(Me2NPhCOO)2(O i Pr) 10 , abbreviated as p-Ti4-N, the specific chemical structure is as follows:
[0007]
[0008] B. The structural formula of ionic titanium oxide cluster polymer is Ti4O2(Me2NPhCOO)2(O i Pr) 10 (C4H6)Br2, abbreviated as p-Ti4-N-Br, has the following specific chemical structure:
[0009] n is an integer greater than 1.
[0010] The second aspect of the present invention provides a method for preparing the above-mentioned titanium oxide cluster compound and ionic titanium oxide cluster polymer.
[0011] The titanium oxide cluster p-Ti4-N in the present invention has the following synthesis method:
[0012]
[0013] The two dimethylaminobenzoic acids involved in the coordination in the titanium oxide cluster are at an open angle, which is suitable for making ionic polymers.
[0014] The titanium oxide cluster p-Ti4-N is reacted with 1,4-dibromo-2-butene by low temperature heating under the protection of inert gas to obtain an ionic titanium oxide cluster polymer p-Ti4-N-Br. The ionic titanium oxide cluster polymer p-Ti4-N-Br of the present invention has the following synthesis method:
[0015]
[0016] In a third aspect of the present invention, the above-mentioned titanium oxide cluster compound and ionic titanium oxide cluster polymer are used as electron transport materials respectively.
[0017] The fourth aspect of the present invention provides a method for preparing an organic solar cell device, wherein the electron transport layer material used in the device preparation is the above-mentioned titanium oxide cluster compound. The present invention provides a method for preparing an organic solar cell device, wherein the electron transport layer material used in the device preparation is the above-mentioned ionic titanium oxide cluster polymer.
[0018] The fifth aspect of the present invention provides a method for preparing an organic solar cell device, and designs two ternary active layer systems based on PM6:BTP-BO-4Cl, in which the above-mentioned ionic titanium oxide cluster polymer is used as an electron transport layer in the preparation of the device. The two ternary active layer systems based on PM6:BTP-BO-4Cl are PM6:BTP-BO-4Cl:PC71BM and PM6:BTP-BO-4Cl:Y6-1O ternary active layer systems.
[0019] The beneficial effects of the present invention are:
[0020] (1) The ionic titanium oxide cluster polymer of the present invention has good alcohol solubility, excellent film-forming property and suitable energy level matching, and is an electron transport layer material with excellent performance. When used in the preparation of solar cell forward devices, it can make the energy conversion efficiency of organic solar cells reach 17.9%.
[0021] (2) The titanium oxide cluster compound of the present invention has mild preparation conditions, simple preparation steps, easy-to-obtain raw materials, low cost, and clear cluster structure. The ionic titanium oxide cluster polymer obtained by one-step synthesis using the titanium oxide cluster compound as a precursor has a simple synthesis method and excellent device performance, and is an ideal electron transport layer material; and the material is used in the ternary active layer systems of PM6:BTP-BO-4Cl:PC71BM and PM6:BTP-BO-4Cl:Y6-1O, respectively, to obtain energy conversion efficiencies of 17.679% and 17.779%. The ionic titanium oxide cluster polymer has demonstrated good practicality and excellent device performance in solar cell devices of different non-fullerene systems, which will help promote the commercialization of organic solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the powder X-ray diffraction pattern of the titanium oxide cluster p-Ti4-N of the present invention;
[0023] Figure 2 The titanium oxide cluster p-Ti4-N of the present invention 1 H-NMR spectrum;
[0024] Figure 3 This is the infrared spectrum of the titanium oxide cluster p-Ti4-N of the present invention;
[0025] Figure 4 It is the ultraviolet-visible absorption spectrum of the titanium oxide cluster p-Ti4-N of the present invention;
[0026] Figure 5 is a schematic structural diagram of an organic solar cell device in the present invention;
[0027] Figure 6 The JV curve of the organic solar cell device in which the titanium oxide cluster p-Ti4-N is used as an electron transport layer in the binary PM6:BTP-BO-4Cl system of the present invention;
[0028] Figure 7 This is the infrared spectrum of the ionic titanium oxide cluster polymer p-Ti4-N-Br of the present invention;
[0029] Figure 8 The GPC spectrum of the p-Ti4-N-Br ionic titanium oxide cluster polymer of the present invention;
[0030] Fig. 9 It is the UV-visible absorption spectrum of the p-Ti4-N-Br ionic titanium oxide cluster polymer of the present invention;
[0031] Fig.10The JV curve of an organic solar cell device using ionic titanium oxide cluster polymer p-Ti4-N-Br as the electron transport layer;
[0032] Fig.11 p-Ti4-N-Br PM6:BTP-BO-4Cl:PC 71 JV curve of BM ternary organic solar cell device;
[0033] Fig.12 JV curves of PM6:BTP-BO-4Cl:Y6-1O ternary organic solar cell devices based on p-Ti4-N-Br. DETAILED DESCRIPTION
[0034] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0035] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0036] Terminology explanation:
[0037] In the present application, PEDOT refers to a polymer of EDOT (3,4-ethylenedioxythiophene monomer).
[0038] PSS is polystyrene sulfonic acid. In view of the cumbersome naming of some compounds, the relevant terms are explained with the help of relevant structural formulas, as follows:
[0039]
[0040]
[0041] The present invention provides a titanium oxide cluster compound and an ionic titanium oxide cluster polymer, wherein:
[0042] A. The molecular structure of titanium oxide cluster compounds is Ti4O2(Me2NPhCOO)2(O i Pr) 10 , abbreviated as p-Ti4-N.
[0043] The titanium oxide cluster p-Ti4-N in the present invention has the following synthesis method:
[0044]
[0045] The two dimethylaminobenzoic acids involved in the coordination in the titanium oxide cluster are at an open angle, which is suitable for making ionic polymers.
[0046] B. The p-Ti4-N titanium oxide cluster was reacted with 1,4-dibromo-2-butene by low temperature heating under the protection of inert gas to obtain an ionic titanium oxide cluster polymer, whose molecular structure is Ti4O2(Me2NPhCOO)2(O i Pr) 10 (C4H6)Br2, abbreviated as p-Ti4-N-Br.
[0047] The ionic titanium oxide cluster polymer p-Ti4-N-Br in the present invention has the following synthesis method:
[0048]
[0049] The specifications of the organic solvents used were all analytical grade.
[0050] The titanium oxide cluster compound and the ionic titanium oxide cluster polymer can be used as electron transport layer materials of organic solar cell devices, wherein the device prepared by using the ionic titanium oxide cluster polymer has better performance.
[0051] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0052] Example 1 The specific preparation steps of the titanium oxide cluster p-Ti4-N are as follows:
[0053] Step 1, add 3–12 mL of isopropanol to a polytetrafluoroethylene reactor containing 0.36–0.73 mmol of 4-dimethylaminobenzoic acid, and perform ultrasonic treatment for 8–20 min;
[0054] Step 2, add 0.16-0.51 mmol of isopropyl titanate to the reactor, quickly cover the reactor, and heat the reactor at 80° C. for 3 days;
[0055] Step 3, naturally cooling to room temperature to obtain a yellow clear liquid, and naturally evaporating and crystallizing at low temperature to obtain light yellow titanium oxide cluster crystals.
[0056] Example 2 The specific preparation steps of the titanium oxide cluster p-Ti4-N are as follows:
[0057] Step 1, add 6 ml of isopropanol to a polytetrafluoroethylene reactor containing 4-dimethylaminobenzoic acid (82.5 mg, 0.50 mmol), and ultrasonicate for 10 min;
[0058] Step 2, add isopropyl titanate (80 mg, 0.27 mmol) to the reactor, quickly cover the reactor, and heat the reactor at 80° C. for 3 days;
[0059] Step 3, naturally cooling to room temperature to obtain a yellow clear liquid, and naturally evaporating and crystallizing at low temperature to obtain light yellow titanium oxide cluster crystals.
[0060] The powder X-ray diffraction pattern of the titanium oxide cluster is as follows: Figure 1 As shown, its 1 H-NMR spectrum Figure 2 Its infrared spectrum is shown in Figure 3 The titanium oxide clusters were dissolved in different mixed solvents to prepare 0.1 mg / mL solutions, and their UV-visible absorption spectra were shown in Figure 4 As shown, the ultraviolet absorption edge in dichloromethane / trifluoroethanol and dichloromethane / isopropanol solutions is about 550 nm, while the ultraviolet absorption edge in dichloromethane / methanol and dichloromethane / ethanol solutions is about 420 nm.
[0061] Example 3 p-Ti4-N is used as an electron transport layer material for PM6:BTP-BO-4Cl binary organic solar cell devices. The specific device preparation steps are as follows:
[0062] Schematic diagram of the device structure of an organic solar cell Figure 5 As shown: The hole transport layer material PEDOT:PSS is spin-coated on the indium tin oxide electrode with a glass substrate, with a thickness of about 30nm. The light-absorbing layer donor PM6 and the acceptor BTP-BO-4Cl are mixed in a mass ratio of 1:1.2, and the light-absorbing layer material is dissolved in chlorobenzene solvent, which contains 0.5% 1,8-diiodooctane; the organic semiconductor light-absorbing layer is spin-coated on PEDOT:PSS with a thickness of about 100nm; the electron transport layer p-Ti4-N is spin-coated with 0.5mg / mL 2,2,2-trifluoroethanol solution to form a film with a thickness of about 5nm, and finally a 90nm Ag electrode is vacuum-evaporated. Under the optimal conditions of the device, an energy conversion efficiency of 17.304% is obtained, with an open circuit voltage (Voc) of 0.839V and a short circuit current density (Jsc) of 26.864mA / cm 2 The filling factor (FF) is 76.754%, which proves that the titanium oxide cluster has good application value as an electron transport layer material in organic solar cells.
[0063] The JV curves of organic solar cell devices with titanium oxide cluster p-Ti4-N as electron transport layer in the binary PM6:BTP-BO-4Cl system are shown in Figure 2. Figure 6 As shown;
[0064] Example 4
[0065] The specific preparation steps of the ionic titanium oxide cluster polymer p-Ti4-N-Br are as follows:
[0066] Step 1, dissolve 100-300 mg of titanium oxide cluster p-Ti4-N in 5-15 mL of chloroform and transfer to a pressure bottle;
[0067] Step 2, add 25-75 mg of 1,4-dibromo-2-butene and 1-5 mL of isopropanol, cover quickly, heat to 80°C in an oil bath, heat and stir for 3 days, and cool naturally to room temperature to obtain an orange solution;
[0068] Step 3, adding a proper amount of petroleum ether to the orange-yellow solution for sedimentation, centrifuging, discarding the supernatant, washing with a small amount of petroleum ether for 3 times, and drying in a vacuum drying oven at low temperature for 1 hour to obtain an ionic titanium oxide cluster polymer.
[0069] Example 5 The specific preparation steps of the ionic titanium oxide cluster polymer p-Ti4-N-Br are as follows:
[0070] Step 1, dissolve the titanium oxide cluster p-Ti4-N (200 mg, 0.175 mmol) in 9 mL of chloroform and transfer it to a 35 mL pressure bottle;
[0071] Step 2, add 1,4-dibromo-2-butene (56 mg, 0.262 mmol) and 2 mL of isopropanol, cover quickly, heat to 80° C. in an oil bath, stir and react for 3 days, and cool naturally to room temperature to obtain an orange solution;
[0072] Step 3, adding a proper amount of petroleum ether to the orange-yellow solution for sedimentation, centrifuging, discarding the supernatant, washing with a small amount of petroleum ether for 3 times, and drying in a vacuum drying oven at low temperature for 1 hour to obtain an ionic titanium oxide cluster polymer.
[0073] The infrared spectrum of the above ionic polymer is shown in Figure 7 As shown, its GPC spectrum is as follows Figure 8 shown.
[0074] The ionic titanium oxide cluster polymer was dissolved in methanol and trifluoroethanol respectively to prepare a 0.1 mg / mL solution, and its UV-visible absorption spectrum was as shown in FIG. Fig. 9 As shown, the ultraviolet absorption edge in methanol is about 430nm, while the ultraviolet absorption edge in trifluoroethanol is about 550nm.
[0075] Example 6p-Ti4-N-Br is used as the electron transport layer for PM6:BTP-BO-4Cl binary organic solar cell devices. The specific device preparation steps are as follows:
[0076] Schematic diagram of the device structure of an organic solar cell Figure 5 As shown: The hole transport layer material PEDOT:PSS is spin-coated on the indium tin oxide electrode with a glass substrate, with a thickness of about 30nm. The light-absorbing layer donor PM6 and the acceptor BTP-BO-4Cl are mixed in a mass ratio of 1:1.2, and the light-absorbing layer material is dissolved in chlorobenzene solvent, which contains 0.5% 1,8-diiodooctane; the organic semiconductor light-absorbing layer is spin-coated on PEDOT:PSS, with a thickness of about 100nm; the electron transport layer material P-Ti4-N-Br is spin-coated with 0.9mg / mL 2,2,2-trifluoroethanol solution to form a film with a thickness of about 10nm, and finally a 90nm Ag electrode is vacuum-evaporated. Under the optimal conditions of the device, an energy conversion efficiency of 17.888% is obtained, with an open circuit voltage (Voc) of 0.847V and a short circuit current density (Jsc) of 27.178mA / cm 2 The filling factor (FF) is 77.745%, which proves that the ionic titanium oxide cluster polymer has excellent performance in the preparation of organic solar cell devices and is an ideal electron transport layer material.
[0077] The JV curves of organic solar cell devices with p-Ti4-N-Br as electron transport layer in the binary PM6:BTP-BO-4Cl system are shown in Figure 2. Fig.10 shown.
[0078] Example 7 PM6:BTP-BO-4Cl:PC with p-Ti4-N-Br as electron transport layer 71 BM ternary organic solar cell device, the specific device preparation steps are as follows:
[0079] The specific device structure diagram of organic solar cells is shown in Figure 5 As shown: The hole transport layer material PEDOT:PSS is spin-coated on the indium tin oxide electrode with a glass substrate, with a thickness of about 30nm. The light absorption layer material PM6: BTP-BO-4Cl:PC 71BM was mixed in a mass ratio of 1:1.1:0.1, and the light-absorbing layer material was dissolved in chlorobenzene solvent, which contained 0.4% 1,8-diiodooctane; the organic semiconductor light-absorbing layer was spin-coated on PEDOT:PSS with a thickness of about 100nm; the electron transport layer material P-Ti4-N-Br was spin-coated with 0.7mg / mL 2,2,2-trifluoroethanol solution, and finally a 90nm Ag electrode was vacuum-evaporated. Under the optimal conditions of the device, an energy conversion efficiency of 17.679% was obtained, with an open circuit voltage (Voc) of 0.850V and a short circuit current density (Jsc) of 26.729mA / cm 2 The filling factor (FF) is 77.785%, which proves that the ionic titanium oxide cluster polymer has good 71 In terms of the preparation of BM ternary organic solar cell devices, its performance is very similar to that of PM6:BTP-BO-4Cl binary organic solar cell devices, and it is also an electron transport layer material suitable for the preparation of ternary organic solar cell devices.
[0080] p-Ti4-N-Br PM6:BTP-BO-4Cl:PC 71 The JV curve of BM ternary organic solar cell device is shown in Fig.11 shown.
[0081] Example 8 PM6:BTP-BO-4Cl:Y6-1O ternary organic solar cell device with p-Ti4-N-Br as electron transport layer, the specific device preparation steps are as follows:
[0082] Schematic diagram of the device structure of an organic solar cell Figure 5 As shown: The hole transport layer material PEDOT:PSS is spin-coated on the indium tin oxide electrode with a glass substrate, with a thickness of about 30nm. The light absorbing layer material PM6:BTP-BO-4Cl:Y6-1O is mixed in a mass ratio of 1:1.07:0.13, and the light absorbing layer material is dissolved in chlorobenzene solvent, which contains 0.4% 1,8-diiodooctane; the organic semiconductor light absorbing layer is spin-coated on PEDOT:PSS, with a thickness of about 100nm; the electron transport layer material P-Ti4-N-Br is spin-coated with 0.7mg / mL 2,2,2-trifluoroethanol solution, and finally a 90nm Ag electrode is vacuum-evaporated. Under the optimal conditions of the device, an energy conversion efficiency of 17.779% is obtained, with an open circuit voltage (Voc) of 0.851V and a short circuit current density (Jsc) of 26.846mA / cm 2The filling factor (FF) is 77.816%, which proves that the ionic titanium oxide cluster polymer has excellent performance in the preparation of PM6:BTP:Y6-1O ternary organic solar cell devices, and the performance difference with PM6:BTP-BO-4Cl binary organic solar cell devices is very small. It is an ideal electron transport layer material suitable for the preparation of PM6:BTP:Y6-1O ternary organic solar cell devices.
[0083] The JV curve of PM6:BTP-BO-4Cl:Y6-1O ternary organic solar cell device of p-Ti4-N-Br is shown in Fig.12 shown.
[0084] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of them with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A titanium oxide cluster compound, characterized in that: Structural formula Ti4O2(Me2NPhCOO)2(O i Pr) 10 , abbreviated as p-Ti4-N, the specific chemical structure is as follows:
2. The method for preparing the titanium oxide cluster according to claim 1, wherein the preparation comprises the following steps: Step 1, adding isopropanol to a polytetrafluoroethylene reaction kettle containing 4-dimethylaminobenzoic acid, and ultrasonicating, wherein the amount ratio of 4-dimethylaminobenzoic acid to isopropanol is (0.36-0.73 mmol): (3-12 mL); Step 2, adding isopropyl titanate to the reactor, quickly covering the reactor, heating the reactor at 80°C for 3 days, and then cooling the reactor naturally to room temperature to obtain a yellow clear liquid, wherein the molar ratio of 4-dimethylaminobenzoic acid to isopropyl titanate is (0.36-0.73 mmol): (0.16-0.51 mmol), and ultrasonicating for 8-20 min; Step 3, subjecting the yellow clarified liquid to low temperature evaporation and crystallization to obtain light yellow titanium oxide cluster crystals.
3. The method for preparing titanium oxide clusters according to claim 2, characterized in that: In step 1, the dosage ratio of 4-dimethylaminobenzoic acid: isopropanol is 0.50mmol:6ml, and ultrasonic treatment is performed for 10 minutes; in step 2, the molar ratio of 4-dimethylaminobenzoic acid to isopropyl titanate is 2:
1.
4. Use of the titanium oxide cluster as claimed in claim 1 in an organic solar cell device, that is, the titanium oxide cluster is used as an electron transport layer material.
5. The titanium oxide cluster p-Ti4-N as claimed in claim 1 is used as an electron transport layer material for an organic solar cell device, characterized in that: The steps for preparing the device include: (1) The hole transport layer material PEDOT:PSS was spin-coated on the indium tin oxide electrode with a glass substrate, with a thickness of 30nm; (2) The light absorption layer donor PM6 and the acceptor BTP-BO-4Cl were mixed in a mass ratio of 1:1.2, and the light absorption layer material was dissolved in chlorobenzene solvent, and the chlorobenzene solvent contained 0.5% 1,8-diiodooctane; (3) The organic semiconductor light absorption layer was spin-coated on PEDOT:PSS with a thickness of 100nm; (4) The electron transport layer p-Ti4-N was spin-coated with 0.5mg / mL 2,2,2-trifluoroethanol solution to form a film with a thickness of 5nm; (5) A 90nm Ag electrode was vacuum-evaporated.
6. An ionic titanium oxide cluster polymer, characterized in that Its structural formula is Ti4O2(Me2NPhCOO)2(O i Pr) 10 (C4H6)Br2, abbreviated as p-Ti4-N-Br, has the following specific chemical structure: n is an integer greater than 1.
7. The method for preparing the ionic titanium oxide cluster polymer according to claim 6, wherein the preparation comprises the following steps: Step 1, dissolving the titanium oxide cluster p-Ti4-N in chloroform and transferring it into a pressure-resistant bottle; Step 2, add 1,4-dibromo-2-butene and isopropanol to the pressure bottle, cover it quickly, heat it in an oil bath to 80°C, heat and stir to react for 3 days, and cool it naturally to room temperature to obtain an orange solution; Step 3, adding petroleum ether to the orange-yellow solution for sedimentation, centrifuging, discarding the supernatant, washing with petroleum ether, and drying under low temperature vacuum to obtain an ionic titanium oxide cluster polymer p-Ti4-N-Br.
8. The method for preparing the ionic titanium oxide cluster polymer according to claim 7, characterized in that: In step 1, the ratio of titanium oxide cluster p-Ti4-N to chloroform is (0.087–0.263 mmol): (5–15 mL); in step 2, the ratio of 1,4-dibromo-2-butene to isopropanol is (0.117–0.351 mmol): (1–5 mL).
9. The method for preparing the ionic titanium oxide cluster polymer according to claim 8, characterized in that: In step 1, the ratio of titanium oxide cluster p-Ti4-N to chloroform is 0.175 mmol:9 mL; in step 2, the ratio of 1,4-dibromo-2-butene to isopropanol is 0.262 mmol:2 mL.
10. Use of the ionic titanium oxide cluster polymer according to claim 6 in an organic solar cell device, that is, the ionic titanium oxide cluster polymer is used as an electron transport layer material.
11. The ionic titanium oxide cluster polymer according to claim 6 is used as an electron transport layer material for an organic solar cell device, characterized in that: The steps for preparing the device include: (1) Spin-coat the hole transport layer material PEDOT:PSS on the glass-based indium tin oxide electrode with a thickness of 30nm; (2) Mix the light absorbing layer donor PM6 and the acceptor BTP-BO-4Cl in a mass ratio of 1:1.2, and use chlorobenzene solvent to dissolve the light absorbing layer material, and the chlorobenzene solvent contains 0.5% 1,8-diiodooctane; (3) Spin-coat the organic semiconductor light absorbing layer on PEDOT:PSS with a thickness of 100nm; (4) Spin-coat the electron transport layer material P-Ti4-N-Br with 0.9mg / mL 2,2,2-trifluoroethanol solution to form a film with a thickness of 10nm; (5) Vacuum thermal evaporation of 90nm Ag electrode.
12. The ionic titanium oxide cluster polymer according to claim 6 is used as an electron transport layer material for an organic solar cell device, characterized in that: The steps for preparing the device include: (1) The hole transport layer material PEDOT:PSS was spin-coated on the indium tin oxide electrode with a glass substrate, with a thickness of 30nm; (2) The light absorption layer materials PM6:BTP-BO-4Cl:PC71BM were mixed in a mass ratio of 1:1.1:0.1, and the light absorption layer materials were dissolved in chlorobenzene solvent, which contained 0.4% 1,8-diiodooctane; (3) The organic semiconductor light absorption layer was spin-coated on PEDOT:PSS, with a thickness of 100nm; (4) The electron transport layer material P-Ti4-N-Br was spin-coated using 0.7mg / mL 2,2,2-trifluoroethanol solution to form a film with a thickness of 10nm; (5) A 90nm Ag electrode was vacuum-evaporated.
13. The ionic titanium oxide cluster polymer according to claim 6 is used as an electron transport layer material for an organic solar cell device, characterized in that: The steps for preparing the device include: (1) The hole transport layer material PEDOT:PSS was spin-coated on the indium tin oxide electrode with a glass substrate, with a thickness of 30nm; (2) The light absorption layer materials PM6:BTP-BO-4Cl:Y6-1O were mixed in a mass ratio of 1:1.07:0.13, and the light absorption layer materials were dissolved in chlorobenzene solvent, which contained 0.4% 1,8-diiodooctane; (3) The organic semiconductor light absorption layer was spin-coated on PEDOT:PSS, with a thickness of 100nm; (4) The electron transport layer material P-Ti4-N-Br was spin-coated using 0.7mg / mL 2,2,2-trifluoroethanol solution to form a film with a thickness of 10nm; (5) A 90nm Ag electrode was vacuum-evaporated.
Citation Information
Patent Citations
Novel pyrrole-3-carboxylic acid-containing titanium oxide cluster monomer C34H64O13N2Ti3 and preparation method thereof
CN107827923A
Titanium-oxygen cluster type compound, preparation thereof and application of titanium-oxygen cluster type compound as electron transport material
CN113480569A